If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 60 = 6y Solving 60 = 6y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-6y' to each side of the equation. 60 + -6y = 6y + -6y Combine like terms: 6y + -6y = 0 60 + -6y = 0 Add '-60' to each side of the equation. 60 + -60 + -6y = 0 + -60 Combine like terms: 60 + -60 = 0 0 + -6y = 0 + -60 -6y = 0 + -60 Combine like terms: 0 + -60 = -60 -6y = -60 Divide each side by '-6'. y = 10 Simplifying y = 10
| x^3+10x^2+41x+50=0 | | 3a^2-6a=0 | | 5-0.6k=5 | | 8x-1=9+9x | | -16+2=-2(x+2) | | 3(2x-7y+1)-3=x-5y+2 | | (7+z)(3z-8)=0 | | -0.6+3.88=-0.8x+0.68 | | 5+2a=3a | | 13a+a^2+40=0 | | -9x-3=60 | | 27-4m=3 | | 6(2x+1)+2=2(4x+1)+2(2x+3) | | 9z-8z=5z+7+3z | | 0=16t^2+8+15 | | 40=(2x-1) | | 10x+5y=95 | | 9C=5F-160 | | -7a-10a= | | 4x+2=7x+7 | | -2x^2+10x-1=0 | | 3=z+6 | | 125w^6+27g^3=0 | | 3x^4-15x^2-72=0 | | 18x^2+15x=0 | | -20+7z+6z^2=0 | | 7x+15= | | 2x^2-7x=-6 | | 6t^2-96=0 | | 18x^2+21x=0 | | 7+2t+3t= | | -6wx^5(3w^6+4w^3x^4-9x^4)= |